Edukasi Penanganan Nyeri Punggung Bawah pada Ibu Hamil melalui Kompres Hangat Water Bag - Faozi, Lukman Aqil; Ningrum, Ema Wahyu; Triana, Noor Yunida (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Back pain is common during pregnancy, especially in the second and third trimesters. Pregnancy-related back pain has become a complex problem, an unpleasant emotional and sensory experience resulting from actual or potential tissue damage. Pain reduction techniques can be pharmacological or non-pharmacological. Applying a water bag or water pillow to the body is known as a "water bag compress." This is done by conduction, where the heat from the water bag penetrates the body and causes blood vessels to dilate and muscles to relax, thereby reducing or eliminating pain. Objective: The purpose of this community service project is to provide knowledge about discomfort during pregnancy and the application of warm compresses using a water bag to reduce low back pain among pregnant women in Somawangi Village, Mandiraja District. Method: Lectures and discussions were used in this community service program. A 10-item true-false questionnaire was used, with a pre-test administered before implementation and a post-test administered after implementation. Result: In the pre-test, 20 individuals (74.0%) had low knowledge levels, and 7 participants (26.0%) were in the fair knowledge level. In the post-test, 27 participants (100%) were in the good knowledge group, indicating that all participants gained more information about how to use water bags and warm compresses to manage pregnancy pain. Conclusion: This community service project demonstrates that pregnant women are now more knowledgeable about using water bags and warm compresses to relieve back pain during pregnancy.